Diaphragm and its preparation method and application
By grafting non-grafted polyolefins, modified cellulose and acid anhydride polyolefins, the problem of large ion transport resistance and interface resistance in the battery is solved, the wetting and mechanical strength of the separator are improved, and the cycle life of the battery is extended.
Patent Information
- Application Number
- CN202410870066.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-04-04
AI Technical Summary
The existing polyolefin separators have large ion transmission resistance and interface resistance during battery charging and discharging, which reduces the cycle life of the battery, and have poor wetting and insufficient mechanical strength.
The non-grafted polyolefin, dicarboxylic acid and/or polybasic acid modified cellulose and anhydride grafted polyolefin are used to combine. The tight bond between the non-grafted polyolefin and the modified cellulose is promoted through the acid anhydride grafted polyolefin, and the mechanical strength and wettability of the separator are improved.
It achieves good wettability, high mechanical strength, excellent comprehensive performance, extends the cycle life of the battery and improves the electrochemical performance.
Smart Images

Figure CN119764750A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a diaphragm and a preparation method and application thereof. Background Art
[0002] At present, the mainstream diaphragm material is polyolefin material, which has good insulation and certain ion transmission channels. However, polyolefin diaphragms have poor wettability and low adhesion to the pole pieces, which increases the ion transmission resistance and interface resistance during battery charging and discharging, and reduces the cycle life of the battery. In the related art, the adhesion and heat resistance between the diaphragm and the pole piece can be improved by coating and modifying the diaphragm surface, but the wettability is poor and the ion transmission resistance is large; or cellulose diaphragms are directly used to improve the wettability of the diaphragm and reduce the ion transmission resistance, but the cellulose diaphragm has low mechanical strength. Therefore, a diaphragm with good wettability and high mechanical strength is needed. Summary of the invention
[0003] In view of this, the present application provides a diaphragm and a preparation method and application thereof. The diaphragm includes non-grafted polyolefin, cellulose modified with dicarboxylic acid and / or polyacid, and polyolefin grafted with anhydride. The cellulose modified with dicarboxylic acid and / or polyacid improves the wettability of the diaphragm, and the polyolefin grafted with anhydride promotes the formation of a tight bond between the non-grafted polyolefin and the cellulose modified with dicarboxylic acid and / or polyacid, thereby improving the mechanical strength of the diaphragm.
[0004] In a first aspect, the present application provides a separator comprising a non-grafted polyolefin, a cellulose modified with a dicarboxylic acid and / or a polyacid, and a polyolefin grafted with anhydride.
[0005] Optionally, the cellulose modified with dicarboxylic acid and / or polyacid has free carboxyl groups.
[0006] Optionally, the anhydride grafted polyolefin includes maleic anhydride grafted polyolefin.
[0007] Optionally, the mass ratio of the non-grafted polyolefin, the dicarboxylic acid and / or polyacid-modified cellulose and the anhydride-grafted polyolefin is (80-95):(1-10):(1-10).
[0008] Optionally, the weight average molecular weight of the non-grafted polyolefin is 600,000-1,000,000, and the non-grafted polyolefin includes one or more of non-grafted polyethylene and non-grafted polypropylene.
[0009] Optionally, the dicarboxylic acid and / or polyacid-modified cellulose includes one or more of dicarboxylic acid and / or polyacid-modified microcrystalline cellulose, dicarboxylic acid and / or polyacid-modified nanocrystalline cellulose and dicarboxylic acid and / or polyacid-modified cellulose derivatives.
[0010] Optionally, the dicarboxylic acid includes one or more of oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, malic acid, azelaic acid and sebacic acid, and the polyacid includes citric acid.
[0011] Optionally, the contact angle between water and the diaphragm is 90°-150°.
[0012] Optionally, after water contacts the diaphragm for 3 seconds, a contact angle between water and the diaphragm is less than or equal to 90°.
[0013] Optionally, the transverse tensile strength of the diaphragm is greater than or equal to 1500 kgf / cm 2 .
[0014] Optionally, the longitudinal tensile strength of the diaphragm is greater than or equal to 1880 kgf / cm 2 .
[0015] The diaphragm provided in the present application has good wettability, high mechanical strength and good comprehensive performance.
[0016] In a second aspect, the present application provides a method for preparing a diaphragm, comprising:
[0017] The non-grafted polyolefin, dicarboxylic acid and / or polyacid-modified cellulose and anhydride-grafted polyolefin are mixed and then melt-formed to obtain a diaphragm.
[0018] Optionally, the mixing temperature is 150° C.-250° C., and the mixing time is 1 h-5 h.
[0019] Optionally, the dicarboxylic acid and / or polyacid-modified cellulose is prepared by mixing cellulose, dicarboxylic acid and / or polyacid and a catalyst to carry out an esterification reaction.
[0020] Optionally, the cellulose has a crystallinity of 75%-85%.
[0021] Optionally, the catalyst comprises one or more of lipase or esterase.
[0022] Optionally, the molar ratio of the hydroxyl group in the cellulose to the dicarboxylic acid and / or polyacid is 1:(1-1.5).
[0023] Optionally, the temperature of the esterification reaction is 110° C.-150° C., and the time of the esterification reaction is 6 h-48 h.
[0024] The preparation method of the diaphragm provided in the present application is novel, the preparation process is simple, the preparation cost is low, and the prepared product has excellent performance.
[0025] In a third aspect, the present application provides a battery, comprising the diaphragm described in any one of the first aspect or the diaphragm prepared by the preparation method described in any one of the second aspect.
[0026] The battery provided in this application has a long cycle life and good electrochemical performance.
[0027] In a fourth aspect, the present application provides an electrical device, wherein the electrical device comprises the battery described in the third aspect.
[0028] The electrical equipment provided in this application has excellent comprehensive performance and can be realized in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0030] Figure 1 A schematic diagram of the contact angle test between water and a diaphragm provided in one embodiment of the present application;
[0031] Figure 2 A schematic diagram of a cross-sectional structure of a battery provided in one embodiment of the present application;
[0032] Figure 3 This is a scanning electron microscope image of the cross section of the diaphragm prepared in comparative example B-7 of the present application after fracture;
[0033] Figure 4 This is a scanning electron microscope image of the cross section of the diaphragm prepared in comparative example B-4 of the present application after fracture;
[0034] Figure 5 This is a scanning electron microscope image of the cross section of the diaphragm prepared in Example B-4 of the present application after fracture;
[0035] Figure 6 This is a scanning electron microscope image of the cross section of the diaphragm prepared in Example B-8 of the present application after fracture;
[0036] Figure 7 This is a scanning electron microscope image of the cross section of the diaphragm prepared in Example B-1 of the present application after fracture;
[0037] Figure 8 This is a scanning electron microscope image of the cross-section of the diaphragm prepared in Example B-2 of the present application after fracture. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0039] The present application provides a diaphragm, which includes non-grafted polyolefin, cellulose modified by dicarboxylic acid and / or polyacid, and polyolefin grafted by acid anhydride. In the present application, cellulose modified by dicarboxylic acid and / or polyacid has excellent hydrophilicity and hydrophobicity, and compounding it with non-grafted polyolefin can improve the wettability of the diaphragm; polyolefin grafted by acid anhydride with strong affinity for non-grafted polyolefin is used as a compatibilizer to promote the combination of cellulose modified by dicarboxylic acid and / or polyacid and polyacid grafted polyolefin, thereby improving the compatibility between non-grafted polyolefin and cellulose modified by dicarboxylic acid and / or polyacid, enhancing the stress strain of the diaphragm, and making the diaphragm have excellent wettability and good mechanical strength. The diaphragm provided by the present application has good wettability and excellent mechanical properties, which is beneficial to improving the cycle life and electrochemical performance of the battery.
[0040] In one embodiment of the present application, the non-grafted polyolefin has high mechanical strength, which is beneficial to improving the safety performance of the battery. Specifically, the non-grafted polyolefin may include, but is not limited to, one or more of non-grafted polyethylene and non-grafted polypropylene. In one embodiment of the present application, the non-grafted polyolefin may be polyethylene. In another embodiment of the present application, the non-grafted polyolefin may be polypropylene.
[0041] In one embodiment of the present application, the weight average molecular weight of the non-grafted polyolefin is 600000-1000000. Specifically, the weight average molecular weight of the non-grafted polyolefin may be, but is not limited to, 600000, 700000, 800000, 900000 or 1000000, etc. In one embodiment of the present application, the weight average molecular weight of the non-grafted polyolefin may be 600000-820000. In another embodiment of the present application, the weight average molecular weight of the non-grafted polyolefin may be 800000-1000000.
[0042] In one embodiment of the present application, the cellulose modified by dicarboxylic acid and / or polyacid may include, but is not limited to, one or more of dicarboxylic acid and / or polyacid-modified microcrystalline cellulose, dicarboxylic acid and / or polyacid-modified nanocrystalline cellulose, and dicarboxylic acid and / or polyacid-modified cellulose derivatives. In one embodiment of the present application, the cellulose modified by dicarboxylic acid and / or polyacid may be nanocrystalline cellulose modified by dicarboxylic acid and / or polyacid. In another embodiment of the present application, the cellulose modified by dicarboxylic acid and / or polyacid may be microcrystalline cellulose modified by dicarboxylic acid and / or polyacid.
[0043] In one embodiment of the present application, the dicarboxylic acid and / or polyacid-modified cellulose is formed by esterification of raw materials including cellulose and dicarboxylic acid and / or polyacid, the dicarboxylic acid and / or polyacid-modified cellulose has free hydroxyl groups and carboxyl groups, and the structure of the dicarboxylic acid and / or polyacid-modified cellulose is R is -H or R 1 is a single bond or a substituted or unsubstituted divalent alkyl group, at least one of R is Since the structural formula of cellulose is There are three alcoholic hydroxyl groups in cellulose, namely the primary hydroxyl group at the carbon 6 position, and the secondary hydroxyl groups at the carbon 2 and carbon 3 positions. According to the spatial theory, the hydroxyl group at the carbon 6 position will preferentially undergo esterification reaction, followed by esterification reaction with the hydroxyl groups at the carbon 2 and carbon 3 positions. By controlling the ratio of dicarboxylic acid and / or polyacid to cellulose, the degree of substitution of cellulose is adjusted to achieve the control of the degree of esterification of cellulose modified by dicarboxylic acid and / or polyacid, and avoid the reaction of dicarboxylic acid and / or polyacid with the hydroxyl groups at the carbon 2 and carbon 3 positions. In other words, part of the hydroxyl groups in cellulose and part of the carboxyl groups in dicarboxylic acid and / or polyacid undergo esterification reaction, and the formed dicarboxylic acid and / or polyacid modified cellulose has ester groups, free hydroxyl groups and free carboxyl groups. In some embodiments, the substituent group in the substituted or unsubstituted divalent alkyl group may be, but is not limited to, substituted or unsubstituted carboxyl groups, substituted or unsubstituted hydroxyl groups, etc.
[0044] In one embodiment of the present application, cellulose has strong hydrophilicity, cellulose and dicarboxylic acid undergo esterification reaction, part of the hydroxyl groups in cellulose react with part of the carboxyl groups in dicarboxylic acid and / or polyacid to obtain dicarboxylic acid and / or polyacid-modified cellulose, that is, there are ester groups, and part of the free hydroxyl groups and free carboxyl groups in the dicarboxylic acid and / or polyacid-modified cellulose. Subsequently, the anhydride-grafted polyolefin reacts with the free hydroxyl groups in the modified cellulose in the acidic environment provided by the free carboxyl groups, promoting the combination of the modified cellulose and the compatibilizer, connecting the modified cellulose and the non-grafted polyolefin through the compatibilizer, thereby improving the binding force compatibility between the non-grafted polyolefin and the dicarboxylic acid and / or polyacid-modified cellulose, enhancing the stress strain of the diaphragm, and making the diaphragm have both excellent wettability and good mechanical strength.
[0045] In one embodiment of the present application, the anhydride grafted polyolefin may be, but is not limited to, maleic anhydride grafted polyolefin, and the weight average molecular weight of the anhydride grafted polyolefin is 100000-1000000. The molecular structure of the maleic anhydride grafted polyolefin contains polyolefin molecular segments, which can improve the affinity of the anhydride grafted polyolefin and the non-grafted polyolefin, so that the binding force between the anhydride grafted polyolefin and the non-grafted polyolefin is enhanced; at the same time, the maleic anhydride grafted polyolefin contains anhydride groups, which can undergo a ring-opening esterification reaction with free hydroxyl groups in the acidic environment provided by the free carboxyl groups to form ester groups, and form a connection with the dicarboxylic acid and / or polyacid-modified cellulose; therefore, the anhydride grafted polyolefin acts as a bridge to connect the non-grafted polyolefin and the dicarboxylic acid and / or polyacid-modified cellulose, thereby enhancing the compatibility of the non-grafted polyolefin and the dicarboxylic acid and / or polyacid-modified cellulose, and improving the mechanical strength and hydrophilicity of the diaphragm.
[0046] In one embodiment of the present application, the mass ratio of non-grafted polyolefin, dicarboxylic acid and / or polyacid modified cellulose and anhydride grafted polyolefin is (80-95): (1-10): (1-10), and an appropriate mass ratio can improve the mechanical strength and wettability of the separator. Specifically, the mass ratio of non-grafted polyolefin, dicarboxylic acid and / or polyacid modified cellulose and anhydride grafted polyolefin can be, but is not limited to, 80:10:10, 82:9:9, 85:7:8, 88:6:6, 90:7:3, 90:5:5, 92:4:4, 92:3:5 or 95:2:3, etc. In one embodiment of the present application, the mass ratio of non-grafted polyolefin, dicarboxylic acid and / or polyacid modified cellulose and anhydride grafted polyolefin is (80-92): (1-8): (1-6). In another embodiment of the present application, the mass ratio of non-grafted polyolefin, dicarboxylic acid and / or polyacid-modified cellulose and anhydride-grafted polyolefin is (89-95):(6-10):(5-10).
[0047] See also Figure 1 , is a schematic diagram of the contact angle test principle of water and a diaphragm provided in one embodiment of the present application, and the contact angle of water and the diaphragm is 90°-150°. The contact angle α between water and the diaphragm is the angle between the side of the water droplet 20 and the surface of the diaphragm 10, which can be used to measure the hydrophilicity of the diaphragm. The contact angle can be measured using a PGX+ portable contact angle tester. Specifically, the contact angle between water and the diaphragm can be, but is not limited to, 90°, 100°, 110°, 120°, 130° or 150°, etc. In one embodiment of the present application, the contact angle between water and the diaphragm can be 90°-120°. In another embodiment of the present application, the contact angle between water and the diaphragm can be 110°-150°.
[0048] In one embodiment of the present application, after water contacts the diaphragm for 3 seconds, the contact angle between water and the diaphragm is less than or equal to 90°. As the contact time between water and the diaphragm increases, the contact angle between water and the diaphragm decreases, and the diaphragm changes from hydrophobic to hydrophilic, thereby improving the hydrophilicity of the diaphragm, which is beneficial to improving the wettability of the diaphragm with the electrolyte and / or the aqueous coating, thereby improving the ion transfer rate of the diaphragm and reducing the coating difficulty of the coating. Specifically, the contact angle between water and the diaphragm may be, but is not limited to, less than or equal to 90°, less than or equal to 80°, less than or equal to 75°, less than or equal to 70°, less than or equal to 68°, or less than or equal to 65°, etc. In one embodiment of the present application, after contacting for 3 seconds, the contact angle between water and the diaphragm may be less than or equal to 75°. In another embodiment of the present application, after contacting for 3 seconds, the contact angle between water and the diaphragm may be less than or equal to 70°.
[0049] In one embodiment of the present application, the transverse direction (TD) tensile strength of the separator is greater than or equal to 1500 kgf / cm 2 The greater the transverse tensile strength of the separator, the higher the mechanical strength of the separator, which can increase the cycle life of the separator during battery use. Specifically, the transverse tensile strength of the separator can be, but is not limited to, greater than or equal to 1500 kgf / cm 2 , greater than or equal to 1550kgf / cm 2 , greater than or equal to 1600kgf / cm 2 , greater than or equal to 1650kgf / cm 2 , greater than or equal to 1700kgf / cm 2 Or greater than or equal to 1800kgf / cm 2 In one embodiment of the present application, the transverse tensile strength of the diaphragm may be greater than or equal to 1600 kgf / cm 2 In another embodiment of the present application, the transverse tensile strength of the diaphragm may be greater than or equal to 1750 kgf / cm 2 .
[0050] In one embodiment of the present application, the longitudinal tensile strength (MD) of the separator is greater than or equal to 1880 kgf / cm 2 The greater the transverse tensile strength of the diaphragm, the higher the mechanical strength of the diaphragm, which can improve the cycle life and safety performance of the diaphragm during battery use. Specifically, the longitudinal tensile strength of the diaphragm can be, but is not limited to, greater than or equal to 1880 kgf / cm 2 , greater than or equal to 1900kgf / cm 2 , greater than or equal to 1920kgf / cm 2 , greater than or equal to 1950kgf / cm 2 , greater than or equal to 2000kgf / cm 2 Or greater than or equal to 2100kgf / cm 2 In one embodiment of the present application, the longitudinal tensile strength of the diaphragm may be greater than or equal to 1900 kgf / cm 2 In another embodiment of the present application, the longitudinal tensile strength of the diaphragm may be greater than or equal to 2050 kgf / cm 2 .
[0051] In one embodiment of the present application, the fracture strength of the diaphragm material is greater than or equal to 24MPa, which increases the cycle life of the diaphragm material and improves the safety of the battery. Test process: The molten diaphragm raw material is made into a 200mm×20mm×20mm diaphragm material strip sample by injection molding, and the strip sample of the diaphragm material is tested using a tensile testing machine according to GB / T1040-2006, and the sample is pulled apart to obtain its fracture strength. Specifically, the fracture strength of the diaphragm material may be, but is not limited to, greater than or equal to 24MPa, greater than or equal to 25MPa, greater than or equal to 26MPa, greater than or equal to 28MPa, greater than or equal to 30MPa, or greater than or equal to 32MPa, etc. In one embodiment of the present application, the fracture strength of the diaphragm material may be greater than or equal to 26MPa. In another embodiment of the present application, the fracture strength of the diaphragm material may be greater than or equal to 32MPa.
[0052] In one embodiment of the present application, the Young's modulus of the diaphragm material is greater than or equal to 1150MPa, which is beneficial to improve the mechanical properties of the diaphragm and enhance the service life and safety of the battery. Testing process: The molten diaphragm raw material is made into a bone rod-shaped diaphragm material sample, and the bone rod-shaped diaphragm material sample is tested using a tensile testing machine, and the sample is broken to obtain its Young's modulus. Specifically, the Young's modulus of the diaphragm material may be, but is not limited to, greater than or equal to 1150MPa, greater than or equal to 1200MPa, greater than or equal to 1250MPa, greater than or equal to 1300MPa, greater than or equal to 1400MPa, or greater than or equal to 1500MPa, etc. In one embodiment of the present application, the Young's modulus of the diaphragm material may be greater than or equal to 1290MPa. In another embodiment of the present application, the Young's modulus of the diaphragm material may be greater than or equal to 1450MPa.
[0053] The present application also provides a method for preparing a diaphragm, comprising: mixing non-grafted polyolefin, dicarboxylic acid and / or polyacid-modified cellulose and anhydride-grafted polyolefin, and then melt-molding to obtain a diaphragm. The method for preparing the diaphragm provided by the present application is novel, has a simple preparation process, and has a low preparation cost. The diaphragm is formed by reacting raw materials including non-grafted polyolefin, dicarboxylic acid and / or polyacid-modified cellulose and anhydride-grafted polyolefin, and can produce a diaphragm with good wettability and high mechanical strength.
[0054] In one embodiment of the present application, the mixing temperature is 150°C-250°C, and the mixing time is 1h-5h. Appropriate mixing conditions can promote the formation of the diaphragm. Specifically, the mixing temperature may be, but not limited to, 150°C, 160°C, 180°C, 200°C, 220°C or 250°C, etc.; the mixing time may be, but not limited to, 1h, 2h, 3h, 4h or 5h, etc. In one embodiment of the present application, the mixing temperature may be 150°C-200°C, and the mixing time may be 1h-3h. In another embodiment of the present application, the mixing temperature may be 190°C-250°C, and the mixing time may be 2.5h-5h.
[0055] In one embodiment of the present application, melt forming includes melting, casting, longitudinal stretching, transverse stretching, extraction and drying and shaping treatment.
[0056] In one embodiment of the present application, the cellulose modified with dicarboxylic acid and / or polyacid is prepared by mixing cellulose, dicarboxylic acid and / or polyacid and a catalyst to carry out an esterification reaction.
[0057] In one embodiment of the present application, the dicarboxylic acid may be, but is not limited to, one or more of oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, malic acid, azelaic acid, and sebacic acid; the polyacid may be, but is not limited to, citric acid. In one embodiment of the present application, the dicarboxylic acid may be oxalic acid.
[0058] In one embodiment of the present application, the crystallinity of cellulose is 75%-85%. The appropriate crystallinity allows cellulose to have free carboxyl groups and / or hydroxyl groups, which is conducive to the modification of cellulose with dicarboxylic acids and / or polyacids. Specifically, the crystallinity of cellulose can be, but is not limited to, 75%, 77%, 79%, 80%, 82%, 84% or 85%, etc. In one embodiment of the present application, the crystallinity of cellulose can be 75%-80%. In another embodiment of the present application, the crystallinity of cellulose can be 78%-85%.
[0059] In one embodiment of the present application, ball milling is also included before the esterification reaction of cellulose. Since cellulose is a semi-crystalline material, there are crystalline and amorphous states in its structure, and there are a large number of hydrogen bonds between molecules. Ball milling is used to destroy the crystalline state and hydrogen bonds in cellulose, so that a large number of hydroxyl groups are converted into free hydroxyl groups, reducing the crystallinity of cellulose. Appropriate crystallinity can improve the mechanical strength of cellulose.
[0060] In one embodiment of the present application, the ball milling time is 5 min-120 min. The appropriate ball milling time can keep the cellulose in an appropriate crystallinity, thereby improving the mechanical strength of the diaphragm. Specifically, the ball milling time can be, but is not limited to, 5 min, 15 min, 20 min, 40 min, 60 min, 80 min, 100 min or 120 min. In one embodiment of the present application, the ball milling time can be 5 min-80 min. In another embodiment of the present application, the ball milling time can be 60 min-120 min.
[0061] In one embodiment of the present application, the cellulose may include, but is not limited to, one or more of microcrystalline cellulose, nanocrystalline cellulose, and cellulose derivatives. In one example of the present application, the cellulose may be microcrystalline cellulose.
[0062] In one embodiment of the present application, the molar ratio of hydroxyl group to dicarboxylic acid and / or polyacid in cellulose is 1:(1-1.5). An appropriate amount of dicarboxylic acid and / or polyacid can control the hydroxyl group in cellulose from being completely esterified, which is beneficial to the subsequent reaction with polyolefin grafted with anhydride. Specifically, the molar ratio of hydroxyl group to dicarboxylic acid and / or polyacid in cellulose can be, but not limited to, 1:1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5, etc. In one embodiment of the present application, the molar ratio of hydroxyl group to dicarboxylic acid and / or polyacid in cellulose can be 1:(1-1.3). In another embodiment of the present application, the molar ratio of hydroxyl group to dicarboxylic acid and / or polyacid in cellulose can be 1:(1.2-1.5).
[0063] In one embodiment of the present application, the temperature of the esterification reaction is 110°C-150°C, and the time of the esterification reaction is 6h-48h. Suitable esterification reaction conditions can complete the modification of cellulose, so that the modified cellulose has both hydrophilicity and hydrophobicity. Specifically, the temperature of the esterification reaction can be but not limited to 110°C, 120°C, 130°C, 140°C or 150°C, etc.; the time of the esterification reaction can be but not limited to 6h, 10h, 16h, 20h, 26h, 30h, 36h, 40h or 48h, etc. In one embodiment of the present application, the temperature of the esterification reaction can be 110°C-130°C, and the time of the esterification reaction can be 6h-35h. In another embodiment of the present application, the temperature of the esterification reaction can be 120°C-150°C, and the time of the esterification reaction can be 24h-48h.
[0064] In one embodiment of the present application, the catalyst can promote the esterification reaction of cellulose and dicarboxylic acid. Specifically, the catalyst includes one or more of lipase or esterase. In one embodiment of the present application, the catalyst can be lipase. In another embodiment of the present application, the catalyst can be esterase.
[0065] In one embodiment of the present application, a cleaning liquid is used to clean the cellulose modified with dicarboxylic acid and / or polyacid. After the esterification reaction, the dicarboxylic acid remains in the modified cellulose, and the cleaning liquid is used to remove the residual dicarboxylic acid. Specifically, the cleaning liquid may include, but is not limited to, one or more of ethanol, acetone, and water. In one embodiment of the present application, the cleaning liquid may be ethanol, and the number of cleaning times may be 2 to 5 times.
[0066] The present application provides a battery, comprising a diaphragm provided by any of the above embodiments or a diaphragm prepared by the preparation method provided by any of the above embodiments. The diaphragm provided by the present application has good wettability and high mechanical strength, which is conducive to improving the electrochemical performance and cycle life of the battery.
[0067] See also Figure 2, which is a schematic diagram of the cross-sectional structure of a battery provided in one embodiment of the present application. Battery 100 includes a positive electrode sheet 11 and a negative electrode sheet 12, and a separator 10 disposed between the positive electrode sheet 11 and the negative electrode sheet 12. In one embodiment of the present application, the battery also includes an electrolyte. Among them, at least part of the positive electrode sheet and at least part of the negative electrode sheet are immersed in the electrolyte. The electrolyte of the present application is not particularly limited, and can be, but not limited to, various substances that can be used as battery electrolytes in the art.
[0068] The present application also provides an electrical device, which includes the battery described in any of the above embodiments. The electrical device provided by the present application has good cycle performance, high safety performance, and strong market competitiveness. Electrical equipment includes vehicles, electronic equipment, energy storage systems, etc., wherein the electronic equipment may include, for example, mobile phones, tablets, watches, VR glasses, etc. In one embodiment of the present application, the battery can be used in vehicles, which can increase the service life and charging rate of the vehicle, increase the widespread application of new energy vehicles, and facilitate the construction of a green and environmentally friendly environment. In another embodiment of the present application, the battery can also be used in mobile phones, which can reduce the preparation cost of the battery and improve the safety of battery use. The above-mentioned battery of the present application can be arranged in the electrical equipment in the form of a single cell, a battery module, a battery pack, etc.
[0069] The effect of the technical solution of the present application is further illustrated below through specific examples.
[0070] Example A-1
[0071] Take 50g of cellulose in a flask, add 250ml of adipic acid in a round-bottom flask, use lipase as a catalyst, keep stirring at 110°C for 48h to obtain dicarboxylic acid-modified cellulose;
[0072] The mass ratio of dicarboxylic acid-modified cellulose, polyethylene (Mw=800000) and maleic anhydride-grafted polyethylene was 10:85:5, and they were blended. The granulated particles were injection molded into 200mm×20mm×20mm diaphragm material strip samples using a small injection molding equipment. The injection molding parameters were as follows: cavity temperature 180°C, cavity pressure 900bar, holding time 20s, and cooling temperature 40°C.
[0073] Example A-2
[0074] The difference from Example A-1 is that the mass ratio of the dicarboxylic acid-modified cellulose, polyethylene (Mw=800,000) and maleic anhydride-grafted polyethylene is 10:88:2.
[0075] Example A-3
[0076] The difference from Example A-1 is that the mass ratio of the dicarboxylic acid-modified cellulose, polyethylene (Mw=800,000) and maleic anhydride-grafted polyethylene is 10:89:1.
[0077] Example B-1
[0078] Take 50g of cellulose in a flask, add 250ml of adipic acid in a round-bottom flask, use lipase as a catalyst, keep stirring at 110℃ for 6h to obtain dicarboxylic acid modified cellulose;
[0079] Cellulose modified with dicarboxylic acid and / or polyacid, polyethylene (Mw=800000) and maleic anhydride grafted polyethylene were blended in a mass ratio of 10:89:1 to finally prepare a diaphragm.
[0080] Example B-2
[0081] The difference from Example B-1 is that the esterification reaction time is 12 hours.
[0082] Example B-3
[0083] The difference from Example B-1 is that the esterification reaction time is 24 hours.
[0084] Example B-4
[0085] The difference from Example B-1 is that the esterification reaction time is 48 hours.
[0086] Example B-5
[0087] The difference from Example B-1 is that the mass ratio of the dicarboxylic acid-modified cellulose, polyethylene (Mw=800,000) and maleic anhydride-grafted polyethylene is 10:88:2.
[0088] Example B-6
[0089] The difference from Example B-1 is that the mass ratio of dicarboxylic acid-modified cellulose, polyethylene (Mw=800000) and maleic anhydride-grafted polyethylene is 10:88:2, and the esterification reaction time is 12 h.
[0090] Example B-7
[0091] The difference from Example B-1 is that the mass ratio of dicarboxylic acid-modified cellulose, polyethylene (Mw=800000) and maleic anhydride-grafted polyethylene is 10:88:2, and the esterification reaction time is 24 hours.
[0092] Example B-8
[0093] The difference from Example B-1 is that the mass ratio of dicarboxylic acid-modified cellulose, polyethylene (Mw=800000) and maleic anhydride-grafted polyethylene is 10:88:2, and the esterification reaction time is 48 hours.
[0094] Example B-9
[0095] The difference from Example B-1 is that citric acid is used to carry out esterification reaction with cellulose to obtain polyacid-modified cellulose. The mass ratio of citric acid-modified cellulose, polyethylene (Mw=800000) and maleic anhydride-grafted polyethylene is 10:87:3.
[0096] Comparative Example A-1
[0097] The difference from Example B-1 is that the mass ratio of the dicarboxylic acid-modified cellulose, polyethylene (Mw=800,000) and maleic anhydride-grafted polyethylene is 10:90:0.
[0098] Comparative Example B-1
[0099] The difference from Example B-1 is that the mass ratio of the dicarboxylic acid-modified cellulose, polyethylene (Mw=800,000) and maleic anhydride-grafted polyethylene is 10:90:0.
[0100] Comparative Example B-2
[0101] The difference from Example B-1 is that the mass ratio of dicarboxylic acid-modified cellulose, polyethylene (Mw=800000) and maleic anhydride-grafted polyethylene is 10:90:0, and the esterification reaction time is 12 h.
[0102] Comparative Example B-3
[0103] The difference from Example B-1 is that the mass ratio of dicarboxylic acid-modified cellulose, polyethylene (Mw=800000) and maleic anhydride-grafted polyethylene is 10:90:0, and the esterification reaction time is 24 hours.
[0104] Comparative Example B-4
[0105] The difference from Example B-1 is that the mass ratio of dicarboxylic acid-modified cellulose, polyethylene (Mw=800000) and maleic anhydride-grafted polyethylene is 10:90:0, and the esterification reaction time is 48 hours.
[0106] Comparative Example B-5
[0107] The difference from Example B-1 is that only polyethylene is added to prepare the diaphragm.
[0108] Comparative Example B-6
[0109] The difference from Example B-1 is that instead of using dicarboxylic acid-modified cellulose and maleic anhydride-grafted polyethylene, cellulose replaces dicarboxylic acid-modified cellulose, and the mass ratio of cellulose to ultra-high molecular weight polyethylene is 10:90.
[0110] Comparative Example B-7
[0111] The difference from Example B-1 is that fiber bundles are used instead of dicarboxylic acid-modified cellulose, and the mass ratio of cellulose, polyethylene (Mw=800,000) and maleic anhydride-grafted polyethylene is 10:80:10.
[0112] Performance Testing
[0113] The strip samples of diaphragm materials prepared in Examples A-1 to A-3 and Comparative Example A-1 were subjected to mechanical property tests according to GB / T1040-2006. The samples were broken using a universal tensile testing machine to obtain the tensile strength and Young's modulus of the diaphragm materials. The results are shown in Table 1.
[0114] The diaphragms prepared in Examples B-1 to B-9 and Comparative Examples B-1 to B-7 were subjected to mechanical property tests according to GB / T36363-2018. After stacking 10 layers, the diaphragm samples were subjected to puncture strength, longitudinal (MD) tensile strength and transverse (TD) tensile strength tests using a universal tensile testing machine. The test results are shown in Table 2.
[0115] Figure 3 This is a scanning electron microscope image of the cross section of the diaphragm prepared in comparative example B-7 of the present application after fracture. Figure 4 This is a scanning electron microscope image of the cross section of the diaphragm prepared in comparative example B-4 of the present application after fracture. Figure 5 This is a scanning electron microscope image of the cross section of the diaphragm prepared in Example B-4 of the present application after fracture. Figure 6 This is a scanning electron microscope image of the cross section of the diaphragm prepared in Example B-8 of the present application after fracture. Figure 7 This is a scanning electron microscope image of the cross section of the diaphragm prepared in Example B-1 of the present application after fracture. Figure 8 This is a scanning electron microscope image of the cross section of the diaphragm prepared in Example B-2 of the present application after fracture. Figure 3 It can be seen that without using cellulose modified with dicarboxylic acid and / or polyacid, cellulose and polyethylene cannot form a close cross section even in the treatment of anhydride-grafted polyolefin; Figure 4 It can be seen that without the addition of anhydride-grafted polyolefin, the cellulose modified with dicarboxylic acid and / or polyacid cannot be tightly bonded to polyethylene; Figure 5-Figure 8It can be seen that the appropriate esterification time and the appropriate mass ratio of dicarboxylic acid and / or polyacid-modified cellulose, polyethylene and maleic anhydride grafted polyethylene can improve the bonding strength between the dicarboxylic acid and / or polyacid-modified cellulose and polyethylene. When the diaphragm is subjected to external force, the dicarboxylic acid and / or polyacid-modified cellulose and polyethylene jointly bear the stress, thereby improving the mechanical strength of the diaphragm.
[0116] After 10 layers of the diaphragms prepared in Examples B-1 to B-9 and Comparative Examples B-1 to B-7 were stacked, the diaphragm samples were tested using a thickness gauge. The test results are shown in Table 2.
[0117] The diaphragms prepared from Examples B-1 to B-9 and Comparative Examples B-1 to B-7 were tested for the contact angle between water and the diaphragm according to GB / T30693. Test process: Use PGX+ Pocket Goniometer to measure the static contact angle. The pocket goniometer includes a light source, a sample stage, a lens, and a camera. First, fill the tube of the goniometer with distilled water, turn on the pump, and finally let the water droplets fall on the diaphragm sample. The image is captured for 3 seconds; after calibration, it is combined with the image of each sample to record the contact angle. The contact angle measurement is performed using the software "Pocket Goniometer program ver.2.2". Each diaphragm sample is tested five times and the average value is calculated. The test results are shown in Table 3.
[0118] Table 1 Diaphragm material performance test results
[0119] Breaking strength(MPa) Young's modulus (MPa) Example A-1 32.08 1146 Example A-2 28.84 1529 Example A-3 32.30 1189 Comparative Example A-1 24.79 1278
[0120] Table 2 Diaphragm performance test results
[0121]
[0122]
[0123] Table 3 Diaphragm contact angle test results
[0124] Contact angle between water and diaphragm (°) Contact angle between water and membrane after 3s contact (°) Example B-1 96.0 69.8 Example B-2 98.3 71.4 Example B-3 105.4 73.9 Example B-4 108.7 78.2 Example B-5 89.6 60.1 Example B-6 92.1 65.6 Example B-7 97.8 70.2 Example B-8 100.5 72.4 Example B-9 99 70 Comparative Example B-1 101.7 71.2 Comparative Example B-2 105.8 74.6 Comparative Example B-3 110.2 78.3 Comparative Example B-4 116.7 81.2 Comparative Example B-5 130.6 128.5 Comparative Example B-6 120.1 113.8 Comparative Example B-7 118.4 112.6
[0125] According to the diaphragm materials prepared in Examples A-1 to A-3 and Comparative Example A-1, the diaphragm materials provided in the present application formed by the reaction of non-grafted polyolefins, dicarboxylic acids and / or polyacid-modified cellulose and anhydride-grafted polyolefins have high mechanical strength. In the diaphragm materials prepared in Examples A-1 to A-3 and Comparative Example A-1, the mass ratio and esterification time of suitable dicarboxylic acids and / or polyacid-modified cellulose, polyethylene and maleic anhydride-grafted polyethylene can obtain a diaphragm material with suitable mechanical strength. The diaphragm is prepared according to the mass ratio of suitable dicarboxylic acids and / or polyacid-modified cellulose, polyethylene and maleic anhydride-grafted polyethylene to obtain the diaphragms prepared in Examples B-1 to B-9 and Comparative Examples B-1 to B-7, which have high mechanical strength and good wettability, and are conducive to improving the ion mobility of the diaphragm and the coating ability of the coating. According to Example B-1 and Example B-2 to Example B-8, it can be seen that the appropriate mass ratio of dicarboxylic acid-modified cellulose, polyethylene and maleic anhydride-grafted polyethylene, and the esterification reaction time can improve the wetting properties, longitudinal tensile strength and transverse tensile strength of the diaphragm, wherein the esterification reaction time affects the esterification degree of the dicarboxylic acid cellulose, and the appropriate esterification reaction time can make the dicarboxylic acid-modified cellulose have free hydroxyl and carboxyl groups, which is convenient for reacting with the anhydride-grafted polyolefin, thereby improving the compatibility of the dicarboxylic acid-modified cellulose and the non-grafted polyolefin; According to Example B-1 and Example B-9, it can be seen that the appropriate polyacid can modify the cellulose, and the modified cellulose The mechanical strength and wettability of the diaphragm can be improved; according to Example B-1 and Comparative Examples B-1 to B-4, it can be seen that the anhydride grafted polyolefin (maleic anhydride grafted polyethylene) can improve the mechanical strength of the diaphragm, and the appropriate amount of anhydride grafted polyolefin added can further improve the mechanical strength of the diaphragm; according to Example B-1 and Comparative Example B-6, it can be seen that according to the preparation method provided in the present application, the prepared diaphragm has good wettability and mechanical properties, which is beneficial to improving the cycle performance and service life of the battery; according to Example B-1 and Comparative Examples B-6 to B-7, it can be seen that cellulose modified with dicarboxylic acids and / or polyacids can improve the wettability of the diaphragm and improve the mechanical strength of the diaphragm.
[0126] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be noted that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A diaphragm, characterized in that: The separator includes non-grafted polyolefin, dicarboxylic acid and / or polyacid-modified cellulose, and anhydride-grafted polyolefin.
2. The diaphragm according to claim 1, characterized in that The cellulose modified with the dicarboxylic acid and / or polyacid has free carboxyl groups.
3. The diaphragm according to claim 1, characterized in that The anhydride grafted polyolefin includes maleic anhydride grafted polyolefin.
4. The diaphragm according to claim 1, characterized in that The mass ratio of the non-grafted polyolefin, the dicarboxylic acid and / or polyacid-modified cellulose and the anhydride-grafted polyolefin is (80-95):(1-10):(1-10).
5. The diaphragm according to claim 1, characterized in that The weight average molecular weight of the non-grafted polyolefin is 600,000-1,000,000, and the non-grafted polyolefin includes one or more of non-grafted polyethylene and non-grafted polypropylene.
6. The diaphragm according to claim 1, characterized in that The dicarboxylic acid and / or polyacid-modified cellulose includes one or more of dicarboxylic acid and / or polyacid-modified microcrystalline cellulose, dicarboxylic acid and / or polyacid-modified nanocrystalline cellulose and dicarboxylic acid and / or polyacid-modified cellulose derivatives.
7. The diaphragm according to claim 1, characterized in that The dicarboxylic acid includes one or more of oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, malic acid, azelaic acid and sebacic acid, and the polyacid includes citric acid.
8. The diaphragm according to claim 1, characterized in that The contact angle between water and the diaphragm is 90°-150°; after 3s of contact between water and the diaphragm, the contact angle between water and the diaphragm is less than or equal to 90°; the transverse tensile strength of the diaphragm is greater than or equal to 1500kgf / cm 2 ; The longitudinal tensile strength of the diaphragm is greater than or equal to 1880kgf / cm 2 .
9. The method for preparing a diaphragm according to any one of claims 1 to 8, characterized in that: include: The non-grafted polyolefin, dicarboxylic acid and / or polyacid-modified cellulose and anhydride-grafted polyolefin are mixed and then melt-formed to obtain a diaphragm.
10. The preparation method according to claim 9, characterized in that: The mixing temperature is 150° C.-250° C., and the mixing time is 1 h-5 h.
11. The preparation method according to claim 9, characterized in that: The dicarboxylic acid and / or polyacid-modified cellulose is prepared in the following manner: cellulose, dicarboxylic acid and / or polyacid and a catalyst are mixed to carry out an esterification reaction.
12. The preparation method according to claim 11, characterized in that: The crystallinity of the cellulose is 75%-85%; The catalyst comprises one or more of lipase or esterase; The molar ratio of the hydroxyl group in the cellulose to the dicarboxylic acid and / or polyacid is 1:(1-1.5); The temperature of the esterification reaction is 110° C.-150° C., and the time of the esterification reaction is 6 h-48 h.
13. A battery, characterized in that: The battery comprises the diaphragm according to any one of claims 1 to 8 or the diaphragm prepared by the preparation method according to any one of claims 9 to 12.
14. An electrical device, characterized in that: The electrical device comprises the battery according to claim 13.